2022
DOI: 10.1021/acsaem.1c03126
|View full text |Cite
|
Sign up to set email alerts
|

Fe-Rich Ni0.06Fe0.94OOH Nanorods as Efficient Electrocatalysts for the Oxygen Evolution Reaction

Abstract: Developing Fe-rich oxygen evolution reaction (OER) electrocatalysts has remained a challenge due to the structural rigidity of the phases. However, wide distribution of the Fe source around the globe and inexpensiveness compared to other transition metals (Ni, Co, etc.) make their development a priority in electrocatalysis research. Herein, we report the synthesis of a Fe-rich OER electrocatalyst (Ni 0.06 Fe 0.94 OOH) that operates at significantly higher efficiency compared to Nirich materials. A controlled s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
(93 reference statements)
3
5
0
Order By: Relevance
“…The ρRHE value is found to be 0.8, elucidating the OOH (ads) + OH – → OO (ads) + H 2 O + e – mechanism that is predominantly known as a driving force for the PDET step (Figure b). , However, the ρRHE value is found to be 0.71 for the pristine CoC 2 O 4 sample, revealing a lower pH dependence compared to that of CoC 2 O 4 /Ag 2 C 2 O 4 (Figure S22). Correlating our observation with previous reports shows that promoting the PDET mechanism just using a minimal amount of silver inclusion can trigger the OER performance through more number of *OH or *OOH sites that could bring rapid kinetics and lower charge-transfer resistance for alkaline OER. , As mentioned in the Introduction, one of the challenges in the silver-doped electrocatalytic materials for OER is their stability. To evaluate the long-term stability, CoC 2 O 4 /Ag 2 C 2 O 4 was subjected to a 24 h stability experiment using the chronopotentiometry method (Figure c).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The ρRHE value is found to be 0.8, elucidating the OOH (ads) + OH – → OO (ads) + H 2 O + e – mechanism that is predominantly known as a driving force for the PDET step (Figure b). , However, the ρRHE value is found to be 0.71 for the pristine CoC 2 O 4 sample, revealing a lower pH dependence compared to that of CoC 2 O 4 /Ag 2 C 2 O 4 (Figure S22). Correlating our observation with previous reports shows that promoting the PDET mechanism just using a minimal amount of silver inclusion can trigger the OER performance through more number of *OH or *OOH sites that could bring rapid kinetics and lower charge-transfer resistance for alkaline OER. , As mentioned in the Introduction, one of the challenges in the silver-doped electrocatalytic materials for OER is their stability. To evaluate the long-term stability, CoC 2 O 4 /Ag 2 C 2 O 4 was subjected to a 24 h stability experiment using the chronopotentiometry method (Figure c).…”
Section: Resultssupporting
confidence: 87%
“…71,72 However, the ρRHE value is found to be 0.71 for the pristine CoC 2 O 4 sample, revealing a lower pH dependence compared to that of CoC 2 O 4 /Ag 2 C 2 O 4 (Figure S22). 73 Correlating our observation with previous reports shows that promoting the PDET mechanism just using a minimal amount of silver inclusion can trigger the OER performance through more number of *OH or *OOH sites that could bring rapid kinetics and lower charge-transfer resistance for alkaline OER. 37,74 As mentioned in the Introduction, one of the challenges in the silver-doped electrocatalytic materials for OER is their stability.…”
Section: ■ Results and Discussionsupporting
confidence: 87%
“…Because of the restrictions associated with determining the ECSA, researchers have recently employed the BET surface area to normalize the activity and obtain the specific activity. They demonstrated that current is normalized by BET surface area ( j BET ) which is typically employed for powder electrocatalysts [26d] . The BET surface areas of materials were determined by the amount of N 2 gas absorbed and desorption measurements from them (in some cases, CO, O 2 , H 2 , and other gases were also used) [32,33] .…”
Section: Intrinsic Activitymentioning
confidence: 99%
“…6,7 To solve the above problems, Ni−Fe-based bimetallic nanoparticles and composite hybrid nanocatalysts with high electrocatalytic activities were constructed in the past few years. 33 For example, Koppisetti's group 34 synthesized an Fe-rich OER electrocatalyst (Ni 0.06 Fe 0.94 OOH) that operated at a low overpotential of 287 mV compared with FeOOH to provide the benchmark current density of 10 mA•cm −2 . The electrocatalyst also possessed a low Tafel slope of 69 mV•dec −1 and a high selectivity with 92% Faradaic efficiency, which was significantly higher compared with Ni-rich materials.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Koppisetti’s group synthesized an Fe-rich OER electrocatalyst (Ni 0.06 Fe 0.94 OOH) that operated at a low overpotential of 287 mV compared with FeOOH to provide the benchmark current density of 10 mA·cm –2 . The electrocatalyst also possessed a low Tafel slope of 69 mV·dec –1 and a high selectivity with 92% Faradaic efficiency, which was significantly higher compared with Ni-rich materials.…”
Section: Introductionmentioning
confidence: 99%